The peripheral cannabinoid receptor type 1 (CB1) as a molecular target for modulating body weight in man - Porter, Richard (My University, 2021)
The cannabinoid 1 (CB1) receptor regulates appetite and body weight; however, unwanted central side effects of both agonists (in wasting disorders) or antagonists (in obesity and diabetes) have limited their therapeutic utility. At the peripheral level, CB1 receptor activation impacts the energy balance of mammals in a number of different ways: inhibiting satiety and emesis, increasing food intake, altering adipokine and satiety hormone levels, altering taste sensation, decreasing lipolysis (fat break down), and increasing lipogenesis (fat generation). The CB1 receptor also plays an important role in the gut–brain axis control of appetite and satiety. The combined effect of peripheral CB1 activation is to promote appetite, energy storage, and energy preservation (and the opposite is true for CB1 antagonists). Therefore, the next generation of CB1 receptor medicines (agonists and antagonists, and indirect modulators of the endocannabinoid system) have been peripherally restricted to mitigate these issues, and some of these are already in clinical stage development. These compounds also have demonstrated potential in other conditions such as alcoholic steatohepatitis and diabetic nephropathy (peripherally restricted CB1 antagonists) and pain conditions (peripherally restricted CB1 agonists and FAAH inhibitors). This review will discuss the mechanisms by which peripheral CB1 receptors regulate body weight, and the therapeutic utility of peripherally restricted drugs in the management of body weight and beyond
Keywords: cannabinoid 1 (CB1) receptor; appetite and body weight; energy balance of mammals; cannabinoid 1 (CB1) receptor; appetite and body weight; energy balance of mammals; Cancer; Neuroscience